Aplikasi Penitipan Hewan Pada Juanda Petshop Depok Berbasis Website - Johari, Ma’mun; Subana A, Bambang; Qurratu 'Ain, Ghina (CV RIFAINSTITUT, 2024)
Pet sitting services are one of the best solutions for the majority of Indonesian people who have pets but are forced to travel long distances and it is not possible to bring their pets with them. This is seen as a good business opportunity by the owner of Juanda Petshop. However, in carrying out business processes so far they still use manual recording which sometimes causes losses both in terms of material and customer trust. This application is in the form of a website created using the Unified Modeling Language (UML), PHP and HTML programming languages and MySQL database. The development method used is waterfall. The stages in the waterfall method are Requirement Analysis, Design, Implementation, Testing and Maintenance. This application was developed using observation and interview methods. The results of this research are based on application testing accompanied by a testing process using black box and white box as well as a validation process to obtain data samples that can be concluded that the application runs reliably and accurately based on its function to improve service to customers to be faster and more accurate thereby increasing customer satisfaction and trust against Juanda Petshop.